1991
DOI: 10.1227/00006123-199101000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Intracranial Aneurysms Caused by Missiles: Their Presentation and Management

Abstract: Only 30 cases of traumatic intracranial aneurysm (TICA) secondary to missile injury have been reported to date. To these we add 15 more cases. Missile TICAs are often seen on a secondary branch of the middle cerebral artery and are usually accompanied by a intracerebral hematoma (80%) or by an acute subdural hematoma (26%). Fourteen of our cases were secondary to shrapnel injuries and only one was secondary to a bullet. None of the injuries was through-and-through. TICAs may enlarge in time and, seemingly inof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(40 citation statements)
references
References 0 publications
1
35
0
4
Order By: Relevance
“…4,6 This argument was further strengthened by our results, as 3 of 7 TICAs were not identified on initial CTA and DSA performed at the time of admission. According to Bell et al, 5 TICAs can rupture as early as postinjury Day 4 and as late as 32 days after injury.…”
Section: Discussionsupporting
confidence: 55%
“…4,6 This argument was further strengthened by our results, as 3 of 7 TICAs were not identified on initial CTA and DSA performed at the time of admission. According to Bell et al, 5 TICAs can rupture as early as postinjury Day 4 and as late as 32 days after injury.…”
Section: Discussionsupporting
confidence: 55%
“…Studies from the Iran-Iraq conflict and Lebanon have suggested the risk factors for the development of intracranial pseudo-aneurysms, based on entry and exit sites, presence of intracerebral hematoma, wound profile crossing dural compartments, presence of retained fragments, absence of exit wound, presence of hematoma in the distal portion of the trajectory, and presence of delayed parenchymal bleed or SAH 2,5 . Similarly, Amirjamshidi et al have suggested angiography in patients with missile passage through Reil's triangle or transhemispheric injuries, large hematoma at the entry site and multiple shells and bone Figure 5 Comparison of discrimination ability of the individual radiologists and average score by ROC curves.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of intracranial vascular rupture after penetrating brain injury remains largely unknown due to significant mortality caused by severe trauma before admission to a hospital [1][2][3][4][5][6][7] . In those who survive, the aim of the emergent diagnostic strategy is to determine the extent of the intracranial damage and provide crucial information for therapeutic decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…These are usually rare and constitute less than 1% of wide intracranial aneurysm series and can be multiple. [8] Traumatic pseudoaneurysms usually rupture in the third week of the post-traumatic period and are mortal in 50%. [9,10] Pseudoaneurysms can develop in hours to years after penetrating traumas, with an average time to development of two to three weeks.…”
Section: Discussionmentioning
confidence: 99%